THU0339 United Kingdom Research Registry for Rare Bone, Joint and Blood Vessel Diseases (RUDY): Analysis of the First 133 Patients. (9th June 2015) - Ponte, C.; Gray, D.; Barrett, J.; Turner, A.; Teare, H.; Hogg, J.; Gray, N.; Harnett, E.; Ropert, R.; Sharma, V.; Lang, G.; Wordsworth, P.; et al.
Abstract : Background: There are around 450 rare bone diseases and 10 main types of vasculitis with differing impact on patients and health services. Historically, tests and treatments designed for more common disorders have been applied to both sets of conditions with variable results. Rudy is a recent NIHR funded UK research registry, with strong emphasis on patients' self-reported outcomes, which aims to create a national cohort of patients with rare diseases of the bone, joints and blood vessels. The long term vision is to enable large scale genetics and epidemiology studies and facilitate patient recruitment for clinical trials and biomarker studies. Objectives: To analyse the patient self-reported outcome data registered in RUDY up to January 2015. Methods: Collaboration between the National Health Service, Academia, Industry and patients' associations was established. Participants with a clinical diagnosis of a rare disorder of the bones, joints or blood vessels with a prevalence of less than 1:5000 were recruited using a web based platform. The diagnosis and demographics were registered and one set of questionnaires was offered for completion to all patients. Results: There were 133 patients (71% females) registered; mean age 44.6±18.1 years [3-81] with 10 patients <18 years. Rare bone or joint disorders were more frequent (65%), particularly fibrous dysplasia. The most common diagnosis of vasculitis was granulomatosis with polyangiitis (GPA) (49%) [Table ]. On line assessments of general health were performed: EQ5D-5L was completed by 56% of patients with a mean score of 2.2±1.2 in mobility, 1.6±0.9 in self-care, 2.1±1.1 in usual activities, 2.6±0.9 in pain/discomfort and 1.8±0.8 in anxiety/depression (range 0-4, best to worst) and 68.4±19.9 general health (range 0-100, worst to best); SF-36 by 53% of patients with a mean score of 47.1±40.3 in physical functioning, 29.3±45.5 in limitations due to physical health, 58.1±49.3 in limitations due to emotional problems, 40.6±27.3 in energy/ fatigue, 69.2±26.1 in emotional wellbeing, 61.3±29.5 in social functioning, 53.9±28.1 in pain and 40.2±30.0 in general health (range 0-100, worst to best); Nottingham ADL score by 59% of patients with a mean score of 19.1±3.9 (range 0-22, worst to best); and Pittsburgh Sleep Quality Index by 56% of patients with a mean score of 9.8±4.0 (range 0-21, best to worst). Pain was further assessed through the Pain detect and McGill pain questionnaires in 53% of patients. Paediatric participants have recently been asked to fill the Childhood Health Assessment, Paediatric Quality of Life and Wong-Baker faces' questionnaires. Other disease specific questionnaires, prospective evaluation of the outcome measures assessed, and the construction of a bone fracture map and a family tree for relatives to participate in are being developed. Conclusions: The RUDY project provides an easy way to collect valuable data and facilitate research on patients with rare diseases of bone and in the vasculitides. A significant proportion of patients reported impairment in several domains of their quality of life and function, highlighting the need for a better understanding of these conditions. Disclosure of Interest: None declared